2018
DOI: 10.1016/j.bbmt.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Moral Distress, Work–Life Balance, and Career Satisfaction among Hematopoietic Cell Transplantation Professionals

Abstract: A projected shortage of hematopoietic cell transplantation (HCT) health professionals was identified as a major issue during the National Marrow Donor Program/Be The Match System Capacity Initiative. Work-related distress and work-life balance were noted to be potential barriers to recruitment/retention. This study examined these barriers and their association with career satisfaction across HCT disciplines. A cross-sectional, 90-item, web-based survey was administered to advanced practice providers, nurses, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
153
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(161 citation statements)
references
References 49 publications
(86 reference statements)
5
153
1
2
Order By: Relevance
“…The overall estimates of the prevalence of burnout based on individual MBI subscales ranged from 8% to 53% (Figure ). This is a broader range of prevalence than reported by individual studies, which cited overall burnout ranging from 52% to 61% using a composite of one or more MBI subscales (Table ) …”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The overall estimates of the prevalence of burnout based on individual MBI subscales ranged from 8% to 53% (Figure ). This is a broader range of prevalence than reported by individual studies, which cited overall burnout ranging from 52% to 61% using a composite of one or more MBI subscales (Table ) …”
Section: Resultsmentioning
confidence: 82%
“…The 15 included articles were all cross‐sectional studies by design, involving a total of 6342 US‐based pharmacists and were published between 1982 and 2018 . There were two sets of articles that were published using the same sample and were analyzed as one data set each .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal Accomplishment subscale results were high, perhaps indicating a factor of pediatric nursing that increases resilience despite moderate burnout in other domains. In studies that compared nurses who work in pediatric units to other in-patient units, burnout results were mixed [26,32,35,36,38,74,78,94]. The majority of the included studies identified correlational relationships using cross-sectional study designs, which limited causal inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout was found to be high in certain high-acuity pediatric units including emergency, medical/surgical, surgery, pediatric intensive care unit (PICU), and neonatal intensive care unit (NICU) [26,32,35,36,76,88]. Davis et al [38] found that adult oncology nurses had higher personal accomplishment than pediatric oncology nurses while Neumann et al [74] found nurses who care for both pediatric and adult patients had lower emotional exhaustion than those who cared for adult patents only. Conversely, Sun et al [94] found that nurses who worked in adult obstetrics and gynecology units had more burnout than nurses who worked in pediatric units; however, Ohue et al [78] reported the inverse.…”
Section: Work Environmentmentioning
confidence: 99%